Microwave and RF Design Networks - Steer, Michael (Open textbook library., 2019)
Microwave and RF Design: Networks presents the tools and techniques required to analyze and design microwave and RF circuits. Because of the finite speed of light, microwave circuits must be considered to be spatially distributed and so there is not a single ground. As such metrics that can be used to describe power flow are of most use. The topics covered include scattering parameters, signal flow graphs, and Smith charts. Acquiring expertise in these is the biggest barriers to a successful career in microwave and RF engineering. This book is suitable as both an undergraduate and graduate textbook, as well as a career-long reference book.